Perbandingan Corporate Governance dengan Sistem One-Tier Board di Inggris dan AS Terkait Efektififas Pencegahan Terjadinya Fraud dalam Korporasi - Rasyidah, Resa (Global and Policy Journal of International Relations, 2013)
ABSTRACTIn general, there are two types of corporate governance systems that are used by countries in the world, the one-tier board system and two-tier board system. The United Kingdom (UK) and The United States (US) are countries that are equally embraced the one-tier board system. However, despite using the same system, there are differences in the results achieved by both countries. When compared with the US that has many cases of corporate fraud to cause a crisis, the UK tends to be quite experienced cases of fraud. This paper is intended to find out why these differences occur. The author states that the factors causing such differences include the type of board structure that is used as well as fraud reporting system.Keyword: Corporate governance, one-tier board system, type of board structure, fraud reporting system.DOI:https://doi.org/10.33005/jgp.v1i01.2006